Refleksi Perilaku Agresif Membuang Sampah Sembarangan dan Tanggapan Masyarakat Sekitar di Kota Denpasar - Benedita Ayu Indah; Afrida Kanata; Mirna Meriati Londong; Jensistro Umbu Pati; Renaldis Halom; Godensia Alfrida Lagur; Mansetus Ganti; Stefanus Jama Nunna; I Made Mahardhika (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article presents a reflection on passive-aggressive behavior in the form of littering, performed by the author as part of a social experiment. The method used was a reflective social experiment approach, where the author acted as the subject performing the behavior in public and recording social responses. Data was collected through field notes and video documentation, then analyzed qualitatively through social psychology perspectives. The aim of the experiment was to observe public responses to the act and to explore how the experience could serve as a means of personal reflection on the social impact of individual behavior. Based on four recorded interactions across public locations, the responses varied from disapproving expressions to direct verbal reprimands. These findings were analyzed through the lens of social psychology theories, particularly passive aggression and social norms. The reflection highlights the importance of individual environmental awareness and encourages respectful public intervention to uphold social order.